Other Bandungs: Afro-Asian Internationalisms in the Early Cold War. - Lewis, Su Lin; Stolte, Carolien (Journal of World History, 2019)
This essay introduces a special issue focused on "Other Bandungs," which moves away from the focus on the high diplomacy of the 1955 Bandung conference to examine other conferences and gatherings across the Afro-Asian world. These gatherings speak to a broader participation of activists, intellectuals, cultural figures, and political leaders in the Afro-Asian moment. This collection thus disrupts hard divisions between state and non-state and warring Cold War blocs, while pointing to the changing social dynamics of internationalism in the Afro-Asian world. This essay points to the material dimensions enhancing and undermining transnational activity, from air travel and passport restrictions to the political economy of conference financing and Cold War patronage. Taken together, this essay frames these articles as an interconnected story of the multiple pulls of cultural and intellectual traffic in the post-colonial era.